THE ROLE OF CULTURAL IDENTITY IN TRANSLATION: A COMPARATIVE STUDY OF UZBEK AND ENGLISH LITERARY TEXTS - Mukhtorjonova Muhsina Yokubjon kizi, (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This article explores the role of cultural identity in the process of literary translation, focusing on the interaction between linguistic form and cultural meaning. The study compares Uzbek and English literary texts to highlight how translators convey national spirit, cultural worldview, and emotional tone. The analysis demonstrates that translation is a form of cultural negotiation, where the translator must balance fidelity to the source with the expectations of the target culture. The findings show that preserving cultural identity enriches intercultural communication and promotes mutual understanding between nations.